APPLICATION OF COMMUNITY SERVICE SENTENCES AFTER ENACTMENT OF LAW NUMBER 1 OF 2023 CONCERNING THE CRIMINAL CODE (NATIONAL CRIMINAL CODE) - Carissa Nuramallia Prihatna; Beniharmoni Harefa (Universitas Serang Raya, 2025)
The implementation of law Number 1 of 2023 concerning the criminal code (National Criminal Code) has several new types of main punishment, one of them is social service, which is further regulated in Article 85 of The National Criminal Code. This research aims to examine and explore how the social service punishment is regulated in The National Criminal Code and how future criminal procedure law would be adjusted to The National Criminal Code in the implementation of social service punishment. The research method that used in this research is normative juridical with statute approach and historical approach, and the existing data results are analyzed a qualitatively by using descriptive writing techniques. This research found that the successful implementation of the social service punishment depends on the readiness of future regulation implementing regulations, particularly the supervision process carried out by Prosecutors and the guidance by Social Workers, and how the Judges obtain data on the social history of defendants when considering sentencing. The establishment of the implementing regulations in the form of a Government Regulation (PP) is urgently needed as an absolute requirement so that the imposition and implementation of social service punishment can be effective, measurable, and capable of overcoming the problem of criminalization in Indonesia. Keywords: National Criminal Code, Social Service Punishment, Criminal Procedure Law